Take a skills-based approach to culture change : applying new skills to meaningful problems at the learning stage helps turn skeptics into evangelists and achieve lasting cultural change - Hugander, Per (MIT Sloan Management Review, 2023)
Typical programs aimed at changing corporate culture to more effectively address organizational challenges often fail to have a lasting effect. Taking a skills-based approach, however, can lead to positive changes in behavior that endure, particularly when it comes to cultivating soft skills like perspective taking. The author explains key attributes of the skills-based approach to culture change and how organizations can leverage it to speed adoption and improve performance in the long term.